How to Design and Implement Powder-To-Tablet Continuous Manufacturing Systems - Muzzio, Fernando; Oka, Sarang (Expertise in Pharmaceutical Process Technology Series, 2022)
How to Design and Implement Powder-to-Tablet Continuous Manufacturing Systems provides a comprehensive overview on the considerations necessary for the design of continuous pharmaceutical manufacturing processes. The book covers both the theory and design of continuous processing of associated unit operations, along with their characterization and control. In addition, it discusses practical insights and strategies that the editor and chapter authors have learned. Chapters cover Process Analytical Technology (PAT) tools and the application of PAT data to enable distributed process control. With numerous case studies throughout, this valuable guide is ideal for those engaged in, or learning about, continuous processing in pharmaceutical manufacturing.